RELATIONSHIP OF ATTITUDE, KNOWLEDGE AND FAMILY SUPPORT FACTORS TO CHI-SQUARE TEST-BASED HYPERTENSION CONTROL EFFORTS - Kurniawan, Aditya; Dewi Arini, Liss Dyah (LPPM Universitas Duta Bangsa Surakarta, 2023)
Hypertension is one of the big challenges in Indonesia. Hypertension is a type of dangerous disease. The urgency of this research is the number of hypertension patients at the Ngoresan Community Health Center, Surakarta which is increasing every year. The objective problem in this research is the increase in the number of hypertension patients every year so that research is needed on the relationship between knowledge, attitudes and family support to efforts to control hypertension. The importance of this research is as an effort to control hypertension which continues to increase every year by means of interviews and distribution of brochures and key chain. The aim of this research is to analyze the factors of knowledge, attitudes and family support towards efforts to control hypertension in patients at the Ngoresan Community Health Center, Surakarta. The stages of this research are cross sectional approach. The sample consisted of 86 respondents. The sampling technique uses the accidental sampling method. The statistical test used is Chi-Square with (Î±=0.05). The results of this research are that there is a relationship between knowledge and efforts to control hypertension with a p-value = 0.003 (<Î±=0.05), there is a relationship between attitudes and efforts to control hypertension with a p-value = 0.011 (<Î±=0.05 ) and there is a relationship between family support and efforts to control hypertension with a p-value = 0.034 (<Î±=0.05).